Aggravation on Criminal Sanction for the Perpetrators of Criminal Corruption Acts on National Fund - Oksidelfa Yanto; H. Muhamad Rezky Pahlawan MP; Suhendar; Samuel Soewita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the forms of corruption committed by state officials to enrich themselves in their activities as public officials and the content of criminal acts for perpetrators in state finances in Indonesian law. The research method used in this paper is a normative legal research method with data collection techniques in the form of secondary data obtained from various kinds of reading materials relevant to the problem. The data can be obtained and collected, processed and analyzed to answer the existing problem. The result of the study is that the form of corruption of public officials is to abuse their authority with elements against the law and result in state financial losses. The contain of criminal weighting for perpetrators of criminal acts of corruption is that the perpetrators can be sentenced to the death penalty by the provisions of the Corruption Crime Act. The weighting of this crime becomes important, robs the people of rights that are contrary to the values of public justice. Indonesia should be able to follow in the footsteps of the Chinese state that death punishes the thieves of state money severely